Engineering Properties of Flaxseed (LC 2063) at Different Moisture - Bhise, Suresh; Kaur, A; Manikantan, M R (Journal of Postharvest Technology, 2013)
Engineering properties of flaxseeds were evaluated as a function of moisture  content. The geometric mean diameter and sphericity of the seed were 3.808  mm and 0.609 respectively. In the moisture range from 10-18% d.b., the length  of the rewetted seed ranged from 4.698 to 4.758 mm, width from 2.400 to  2.360 mm, thickness from 0.999 to 2.157 mm, geometric mean diameter  (GMD) from 2.240 to 2.893 mm, sphericity from 0.477 to 0.478. The thousand  kernel weight (TKW) increased from 7.195 to 7.403 g, bulk density decreased  from 613.818 to 547.174 kg/m3, true density increased from 1105.326 to  1183.200 kg/m3, porosity increased from 44.467 to 49.954 %, hardness  decreased from 74.411 to 40.828 N, initial cracking force decreased from  52.470 to 34.019 N and area ranged from 6.140 to 6.406 Nmm. In the same  moisture range, the static coefficient of friction varied from 0.320 to 0.420 for  different surfaces, while the angle of repose varied from 16.969 to 24.699 for  seed. Lightness (L), a value (red-green axis) and b value (yellow-blue axis) of  seed decreased from 42.94 to 40.360, 7.22 to 4.96, and 10.70 to 8.30,  respectively, with increase in moisture content of seed from 10 to 18 %, d.b.
Keywords: Flaxseed; Moisture; Physical property; Porosity